(untitled) (Proceeding of SINERGY, 2026)
The development of the platform economy has significantly changed the work landscape, particularly for location-based gig workers who face continuous and uncertain spatial changes. This study aims to explore the conceptual relationship between learning agility and geo-occupational well-being in the context of gig workers in organizational development and change. Using a brief literature review method, this study examines previous studies on gig workers, algorithm management, occupational well-being, and learning agility. The results of the review indicate that platform-based organizational change has a strong spatial dimension and directly impacts the affective, cognitive, social, and psychosomatic well-being of gig workers. Learning agility emerges as a crucial adaptive capability that enables workers to learn from cross-location experiences, develop flexible spatial work strategies, and maintain well-being amidst geographic uncertainty. It is found that the integration of learning agility and GOWS provides a relevant framework for understanding individual adaptation in the platform economy, while offering implications for organizational development, platform policy design, and future research agendas.